SPECIFIC FEATURES OF FAMILY, NEIGHBORHOOD, SCHOOL COOPERATION IN INCREASING THE STRONG MOTIVATION OF STUDENTS TO RECEIVE EDUCATION - Mahmudjonov Asror (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In the article, the problem of establishing cooperation with the family, neighborhood, school in increasing the strong motivation of students to receive education was studied, the Joint Action, cooperation, mutual friendship activities of the reader and the public based on mutual agreement were analyzed from a pedagogical and psychological point of view.